Myocardial Energetics in Obesity: Enhanced ATP Delivery Through Creatine Kinase With Blunted Stress Response. Issue 14 (7th April 2020) - Rayner, Jennifer J.; Peterzan, Mark A.; Watson, William D.; Clarke, William T.; Neubauer, Stefan; Rodgers, Christopher T.; Rider, Oliver J.
Abstract : Background: Obesity is strongly associated with exercise intolerance and the development of heart failure. Whereas myocardial energetics and diastolic function are impaired in obesity, systolic function is usually preserved. This suggests that the rate of ATP delivery is maintained, but this has never been explored in human obesity. We hypothesized that ATP transfer rate through creatine kinase (CK) ( k f CKrest ) would be increased, compensating for depleted energy stores (phosphocreatine/ATP), but potentially limiting greater ATP delivery during increased workload. We hypothesized that these changes would normalize with weight loss. Methods: We recruited 80 volunteers (35 controls [body mass index 24±3 kg/m 2 ], 45 obese [body mass index 35±5 kg/m 2 ]) without coexisting cardiovascular disease. Participants underwent body composition analysis, magnetic resonance imaging of abdominal, liver, and myocardial fat content, left ventricular function, and 31 P magnetic resonance spectroscopy to assess phosphocreatine/ATP and CK kinetics, at rest and during dobutamine stress. Obese volunteers were assigned to a dietary weight loss intervention, before reexamination. Results: At rest, although myocardial phosphocreatine/ATP was 14% lower in obesity (1.9±0.3 versus 2.2±0.2, P <0.001), k f Ckrest was 33% higher (0.23±0.07 s –1 versus 0.16±0.08 s –1, P =0.002), yielding no difference in overall resting ATP delivery (obese 2.5±0.9 µmol·g –1 ·s –1 versus control 2.2±1.1 µmol·g –1 ·s –1, P =0.232). In controls, increasing cardiac workload led to an increase in both k f CK (+86%, P <0.001) and ATP delivery (+80%, P <0.001). However, in obesity, similar stress led to no significant increase in either k f CK ( P =0.117) or ATP delivery ( P =0.608). This was accompanied by reduced systolic augmentation (absolute increase in left ventricular ejection fraction, obese +16±7% versus control +21±4%, P =0.031). Successful weight loss (–11±5% body weight) was associated with improvement of these energetic changes such that there was no significant difference in comparison with controls. Conclusions: In the obese resting heart, the myocardial CK reaction rate is increased, maintaining ATP delivery despite reduced phosphocreatine/ATP. During increased workload, although the nonobese heart increases ATP delivery through CK, the obese heart does not; this is associated with reduced systolic augmentation and exercise tolerance. Weight loss reverses these energetic changes. This highlights myocardial energy delivery through CK as a potential therapeutic target to improve symptoms in obesity-related heart disease, and a fascinating modifiable pathway involved in the progression to heart failure, as well. Abstract : Supplemental Digital Content is available in the text.